La fiche du vocabulaire comme aide didactique dans l’enseignement/ apprentissage de la compétence scripturale en FLE Cas des apprenants de 1ère année secondaire - Ilham BENGHIDA (My University, 2022)
Abstract The study conducted by us, we seek to identify the effectiveness and benefits of the vocabulary bond, which allows French learners as a foreign language to learn writing skills and written expression especially in the secondary level. This experiment aims to show the progress made in writing activity, to determine the usefulness of this processing or rather the linguistic basis in teaching/learning the written expression in French as a foreign language in order to begin an analytical study of the outcome we obtained from the experimental sample. study enabled us to confirm the effectiveness of the vocabulary bond and the process of adding this bond has added a lot of pros in writing activities, especially in the FLE class in high school, where we can consider it as an opportunity for learners to systematically select their subject vocabulary and improve their written expression. ----------------- Résumé A travers notre travail de recherche, nous voulons savoir à quel point la fiche de vocabulaire peut-elle être efficace et avantageuse et permet-elle l’amélioration de la compétence scripturale des apprenants en FLE au secondaire. Notre expérimentation vise à montrer le déroulement d’une activité d’écriture, pour déterminer l’utilité de ce traitement dans l’enseignement/apprentissage de l’expression écrite en FLE afin d’entamer une étude analytique des productions du groupe expérimental Il ressort de cette étude, que l’intégration des fiche de vocabulaire dans les activités d’écriture et particulièrement en classe de FLE au secondaire, c’est une occasion aux apprenants pour choisir systématiquement le vocabulaire de leur sujet et améliorer leur expression écrite.